The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1187/cbe.20-05-0091
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Do Study Habits Relate to Performance?

Abstract: Students’ study habits during independent study sessions were examined. Controlling for preparation, total study time, and class absences, it was found that active study strategy use positively predicted exam score, study spacing potential did not predict exam score, and distraction during study sessions negatively predicted exam score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…If the objective is for students to focus on understanding rather than memorizing course materials, writing assessment questions that reflect this objective will encourage students to think deeply about the material and reward those who do. Students may benefit from their instructor explaining how their open-note exams are designed to encourage them to specifically focus on understanding, along with the study habits that have previously been shown to increase student performance and learning (e.g., synthesizing notes, focusing on understanding, self-quizzing [ 25 ]). Second, we encourage biology education researchers to evaluate how open-note exams are commonly designed and implemented in post-secondary biology classrooms, paying special attention to the Bloom’s taxonomy level of each exam question, whether the instructor explains the difference between an open-note and a closed-note exam, and whether the instructor models evidence-based study habits for their students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the objective is for students to focus on understanding rather than memorizing course materials, writing assessment questions that reflect this objective will encourage students to think deeply about the material and reward those who do. Students may benefit from their instructor explaining how their open-note exams are designed to encourage them to specifically focus on understanding, along with the study habits that have previously been shown to increase student performance and learning (e.g., synthesizing notes, focusing on understanding, self-quizzing [ 25 ]). Second, we encourage biology education researchers to evaluate how open-note exams are commonly designed and implemented in post-secondary biology classrooms, paying special attention to the Bloom’s taxonomy level of each exam question, whether the instructor explains the difference between an open-note and a closed-note exam, and whether the instructor models evidence-based study habits for their students.…”
Section: Discussionmentioning
confidence: 99%
“…Study habits include strategies students use to understand and retain class content. They also encompass how much time students spend studying and how students distribute their study time over the class of a semester [24,25]. Because exam performance is highly correlated with study habits [26][27][28][29], the effectiveness of open-note exam taking may rely heavily on the specific exam preparation methods used by students.…”
Section: Introductionmentioning
confidence: 99%
“…College students also reported being distracted 20% of the time during study sessions. Amount of time spent studying, types of strategies used and minimizing distractions are all significant factors that contribute to a students' overall academic performance, which must be further analyzed (13). In relation to specific study strategies, researchers determined common study methods to include completion of past exam questions (100% of students), rereading material (92.3% of students), explaining concepts to peers (7.7% of students), and using flashcards (7.7% of students) (14).…”
Section: Introductionmentioning
confidence: 99%
“…How students do their studies has a significant impact on their degree of academic performance. Students' degree of preparation and learning techniques devised and utilized intentionally has a significant impact on their academic success (Walck-Shannon, 2021). Thus, one of the most important student learning variables that have a significant impact on student's academic success is study habits.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing effective study habits is critical for all students, regardless of their level of schooling. It improves students' capacity to be self-disciplined, self-directed, and productive in their degree programs (Walck-Shannon, 2021). The earlier a student begins exercising and forming excellent habits, the more likely he is to stick with them.…”
Section: Introductionmentioning
confidence: 99%